Hubungan Tingkat Pengetahuan dan Motivasi terhadap Kepatuhan Pengobatan TB di Wilayah Kerja Puskesmas Sungai Sariak - M. Nur, Yulia; Sari, Yade Kurnia; Fitriana, Nora (Jurnal Akademika Baiturrahim Jambi, 2024)
TB patients' knowledge and motivation will have an impact on their compliance in implementing the treatment program. The better a person's knowledge, the more obedient they will be in carrying out quality treatment and the better a person's motivation, the higher a person's enthusiasm will be to achieve healing. The aim of this research is to determine and describe the relationship between knowledge and motivation and treatment compliance in TB sufferers. This type of research is cross-sectional. The population in this study were TB sufferers in the Sungai Sariak Community Health Center working area, namely 75 people, and the total sample was 59 people. The sampling technique used in this research is non-probability sampling with purposive sampling technique. The instrument used in this research was a questionnaire. The type of questionnaire used is a closed questionnaire. Data collection was carried out by means of interviews and filling out questionnaires.  The conclusion of this research is that sufferers' knowledge is in the good category, sufferers' motivation is in the high category, and most TB sufferers are compliant with treatment. There is a relationship between patient knowledge and treatment compliance; There is a relationship between patient motivation and treatment compliance in the Sungai Sariak Community Health Center working area. It is recommended that families and health workers maintain and increase the knowledge and motivation of TB patients to always control treatment compliance, so that drug withdrawal and resistance do not occur, which causes MDR TB.